A longitudinal examination of stressors, appraisals, and coping in youth swimming. (March 2017) - Hayward, Francesca P.I.; Knight, Camilla J.; Mellalieu, Stephen D.
Abstract: Purpose: Involvement in sport has the potential to cause athletes, coaches, and parents to experience stress. However, the extent to which experiences of stress are shared within the athletic triad is unknown. The purpose of this study was to examine the individual and shared stress experiences among youth swimmers, their mothers, and coach within the context of training, tapering, and competition. Design: Multi-case study design. Method: Four female swimmers, their mother, and one coach completed daily diaries for six weeks and up to three semi-structured interviews. Data were analyzed through within- and cross-case thematic analysis. Results: The study showed evidence of shared stress experiences between all three members of the athletic triad. Participants predominately encountered organizational stressors, which they appraised in relation to movements between squad, interpersonal relationships, and overall progress towards performance goals/outcomes. Numerous coping strategies were employed by participants, with varying degrees of effectiveness, such as seeking social support, distancing, and lift sharing. The coping strategies used by coaches, swimmers, and parents were often interrelated with participants frequently seeking emotional support from one another. The majority of stressors and appraisals cited by parents and swimmers were shared, with both heavily relying on social support to help each other cope with the stressors encountered. Conclusion: Athletes, parents, and coaches have the capacity to influence one another's stress experiences and as such their experiences should be considered simultaneously to maximize the impact of interventions. Highlights: This study examined the individual and shared stress experiences of parents, coaches, and adolescent swimmers. A case study approach was adopted. Parents and swimmers shared many stressors and often relied on each other to cope. Coaches, parents, and swimmers appraisals and coping strategies were intricately related. Stress interventions would benefit from fully considering the interpersonal influences on stress experiences.